Directive Speech Acts in Academic Discourse: Ethnography of Communication from Gender Perspective in Higher Education - Fatma Fatma; Harun Joko Prayitno; Norliza Jamaludin; Gautam Kumar Jha; Taha Ibrahim Badri (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
In spoken academic discourse, there are various directive speech acts forms and strategies both formal and informal. Based on the previous research with different focuses show that directive speech acts is one of speech acts types mostly used in daily conversation. The study of directive speech acts can also be found in classroom interaction as spoken academic discourse. The locutors’ and interlocutors’ expressions in spoken academic discourse are vary. Language variation involves direct and indirect strategies as well as literal and non-literal with small portion of local language use. The use of directive speech acts is affected by contextual socio-cultural factors within the conversation. The locutors sometimes use local language in conveying certain meaning to the interlocutors. The structure of dialogue, moreover, disallows the taking up of any position beyond the interlocutors from which they can be integrated into a larger totality.